2003
DOI: 10.1590/s1415-790x2003000400011
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de um Questionário Quantitativo de Freqüência Alimentar (QQFA) para um estudo caso-controle de dieta e câncer de mama em João Pessoa - PB

Abstract: Desenvolvimento de um questionário quantitativo de freqüência alimentar Lima, F.E.L. et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
1
6
0
5
Order By: Relevance
“…20 Meat, rice, and bread were the main sources of energy. Brazilian studies 23,31 have reported similar findings in people living in other Brazilian regions. However, in the target population of this study, meat was a major source of energy, which was twice as much as that reported in a São Paulo study 31 and more than five times higher than that seen in women living in the state of Paraí-ba.…”
Section: Discussionsupporting
confidence: 61%
“…20 Meat, rice, and bread were the main sources of energy. Brazilian studies 23,31 have reported similar findings in people living in other Brazilian regions. However, in the target population of this study, meat was a major source of energy, which was twice as much as that reported in a São Paulo study 31 and more than five times higher than that seen in women living in the state of Paraí-ba.…”
Section: Discussionsupporting
confidence: 61%
“…The sample size was calculated based on a casecontrol study conducted in the city of João Pessoa (Rio Grande do Norte, Brazil), finding an odds ratio (OR) of 4.3 between the consumption of red meat with fat and breast cancer diagnosis [18]. Using a power of 80% for the study and a significance level of 5%, the required number of patients in each study group would be 58 women.…”
Section: Discussionmentioning
confidence: 99%
“…The FFQ was adapted from an instrument validated in Brazil in the same geographical region to assess the consumption of fat in women with breast cancer [18]. This FFQ had 98 food items referent to consumption in the past 12 months.…”
Section: Original Articlementioning
confidence: 99%
“…Development of this questionnaire has already been published 11 . Briefly, a food list was obtained through 24-hour recall (R24h) applied to 100 women (25-79 years of age), clients of public health services.…”
Section: Food Frequency Questionnairementioning
confidence: 99%